India and Bay of Bengal community the BIMSTEC experiment - Devi, T. Nirmala (ed.) (New Delhi, 2007)
Book Summary of India And Bay Of Bengal Community The Bay of Bengal Initiative for Multi Sectoral Techno Economic Cooperation (BIMSTEC) is a sub regional grouping. Formed in 1997 with the main objective of promoting cooperation among the contiguous countries of the Bay of Bengal, the BIMSTEC has identified six agreed areas of cooperation, viz., trade and investment; technology; transport and communication; energy; tourism and fisheries. It is yet a pioneering effort in launching an exclusive collected work on the subject as the literature on the BIMSTEC is very inadequate and wanting. About the Author T. Nirmala Devi, is professor and Director of the Center for SAARC Studies, Andhra University, Visakhapatnam. Table of Contents Foreword Preface List of Contributors Introduction Part-I: Indias Role in BIMSTEC India and BIMST-EC Indias Role in BIMST-EC Indias Trade and Investment Opportunities in BIMSTEC Indias New Regionalism in Asia Part-II: Cooperation in Trade and Investment in BIMSTEC Challenges and Opportunities for BIMSTEC Economic Cooperation in BIMSTEC Regional Economic Arrangements Evolution of BIMSTEC Possibilities of Cooperation in BIMSTEC Country Part-III: Political Perspectives on BIMSTEC Development of BIMST-EC Political and Foreign Policy Perspectives of BIMSTEC Indo-Sri Lanka Maritime Co-operation Re-Envisioning India-Myanmar Relations A Study on Indias Political-Economic Relations with Some BIMSTEC Nations Part-IV: Cooperation in Science and Technology in BIMSTEC Coastal and Oceanic Resources of Bay of Bengal Some Views on Possible Collaboration in Science and Technology among Bay of Bengal Economic Community with Emphasis on Space, Earth and Atmospheric Science International Cooperation in BIMSTEC for Marine Archaeology Part-V: Human Development and other Aspects of BIMSTEC The Asian Drama of BIMSTEC, SAARC, and ASEAN Countries Strategies for the Achie
Keywords: Economic cooperation-India